SARS-CoV-2 attacks the weakest point - COVID-19 course in a pediatric patient with Friedreich's ataxia. (April 2022) - Faltin, Kamil; Lewandowska, Zuzanna; Małecki, Paweł; Czyż, Krzysztof; Szafran, Emilia; Kowalska-Tupko, Agnieszka; Mania, Anna; Mazur-Melewska, Katarzyna; Jończyk-Potoczna, Katarzyna; Bobkowski, Waldemar; Figlerowicz, Magdalena
Highlights: COVID-19 in children with Friedreich's ataxia can induce atrial fibrillation and heart failure. Chronic cardiac disease promotes a severe course of COVID-19 in pediatric patients. Rapid treatment with antiviral therapy is crucial for a good prognosis in COVID-19. Abstract: COVID-19 pandemic is the biggest epidemiologic problem of the 21st century. A severe course of SARS-CoV-2 infection in children is rare. Sometimes, especially in patients with chronic disease, COVID-19 may be insidious and life-threatening. This article presents the course of COVID-19 in a 17-year-old boy with Friedreich's ataxia-induced hypertrophic cardiomyopathy. Although, the main symptoms of COVID-19 (i.e., fever, cough) were moderate at the beginning of the illness, the patient's condition deteriorated rapidly due to cardiac problems, atrial fibrillation, and heart failure. The patient required antiarrhythmic treatment and pharmacological and electrical cardioversion. Moreover, because of pneumonia requiring supplemental oxygen, remdesivir and convalescent plasma therapy was given to the patient., The administration of the antiviral treatment was crucial to the patient's recovery.